Formation of Flavonoid Metabolons: Functional Significance of Protein-Protein Interactions and Impact on Flavonoid Chemodiversity - Nakayama, Toru; Takahashi, Seiji; Waki, Toshiyuki (Frontiers in Plant Science, 2019)
Flavonoids are a class of plant specialized metabolites with more than 6900 known structures and play important roles in plant survival and reproduction. These metabolites are derived from p-coumaroyl-CoA via the sequential actions of a variety of flavonoid enzymes, which have been proposed to form weakly bound, ordered protein complexes termed flavonoid metabolons. This review discusses the impacts of the formation of flavonoid metabolons on the chemodiversity of flavonoids. Specific protein-protein interactions in the metabolons of Arabidopsis thaliana and other plant species have been studied for two decades. In many cases, metabolons are associated with the ER membrane, with ER-bound cytochromes P450 hypothesized to serve as nuclei for metabolon formation. Indeed, cytochromes P450 have been found to be components of flavonoid metabolons in rice, snapdragon, torenia, and soybean. Recent studies illustrate the importance of specific interactions for the efficient production and temporal/spatial distribution of flavonoids. For example, in diverse plant species catalytically inactive type-IV chalcone isomerase-like protein serves as an enhancer of flavonoid production via its involvement in flavonoid metabolons. In soybean roots, a specific isozyme of chalcone reductase (CHR) interacts with 2-hydroxyisoflavanone synthase, to which chalcone synthase (CHS) can also bind, providing a mechanism to prevent the loss of the unstable CHR substrate during its transfer from CHS to CHR. Thus, diversification in chemical structures and temporal/spatial distribution patterns of flavonoids in plants is likely to be mediated by the formation of specific flavonoid metabolons via specific protein-protein interactions.